Mediated political realities: the social imaginary of democracy in the Costa Rican cinema - Madriz Sojo, Gabriel (2016)
This paper discusses and claims the role of cinema as an ideal multidisciplinary object of study to rethink the intricacies of the "tension between politics and culture", understood as a struggle for the construction of meaning in society that is not only built upon the canonical theory of State, but through raised representations that produce the same or greater sense than theory itself. It proposes a political analysis of the films; Caribe (2004) by Esteban Ramírez and El cielo rojo (2008) by Miguel Gómez to study the social imaginary that they pose on Costa Rican democracy in some historical contexts, as a reflection on the forms of political participation and mechanisms established for channeling social demands in a liberal democracy`s regime.